Pengaruh Motivasi Kerja Guru Terhadap Prestasi Belajar Siswa Pada SMP Negeri 2 Mesjid Raya - Nurmalina Nurmalina (JOURNAL OF EDUCATION SCIENCE, 2019)
Motivation of teacher work is an important factor that influences student learning achievement. The purpose of this study was to find out whether there was an effect of teacher work motivation on student achievement in the SMPN 2 Mesjid Raya. This study uses a quantitative approach with descriptive methods. Data collection techniques used were questionnaires, documentation and interviews. Data analysis using correlation techniques and regression with SPSS 16.0 program. The population / sample in this study were all PNS teachers in the Grand Mosque 2 Mesjid Raya which numbered 29 people. The results showed that there was a positive and significant influence between teacher work motivation on student learning achievement seen from the teacher's responsibility in carrying out the task, carrying out the task with a clear target, having the feeling of being happy at work, always trying to fulfill his life needs, working in the hope of wanting. Motivation can be grown through the regulation of the physical environment, regulation, work atmosphere, discipline, encouragement, effective appreciation and the provision of various learning resources through the development of the Learning Resource Center (PSB). With the existence of high motivation from the teacher board is expected to bring a significant impact on improving student learning achievement, this is if the board of teachers want to devote all their mind and energy in helping students.Keywords: Work Motivation, Learning Achievement.